Corporate Social Responsibility, Social and Community Development Program as the Implementation of Gcg at PT PLN (Persero) - Surya Fitriadi (Journal of Accounting and Finance Management, 2020)
The implementation of the Corporate Social Responsibility (CSR) program is one implementation concept of good corporate governance. Good corporate governance regulates the relationships of all stakeholders that can be fulfilled proportionally, avoid mistakes in corporate strategy and ensures that mistakes can be corrected immediately. PT. PLN (Persero) is a State-Owned Company (BUMN), a company engaged in the electric energy has a commitment to improve the quality of people's lives through electricity and make electricity as a driving force for economic activities and environmentally sound businesses. PLN business objectives will be achieved if the Company is able to maintain a balance of economic, social and environmental performances. The obtained economic value is eligible for the benefits of the community, the environment, employees and customers, through quality and sustainable social and environmental responsibility programs Social responsibility programs that meet people’s needs, improve living standards and expand employment opportunities, positive interaction between PLN and the community will increase their sense of belonging and help maintain PLN installations in their residential areas.